Shedding Light on the Venom Proteomes of the Allergy-Relevant Hymenoptera Polistes dominula (European Paper Wasp) and Vespula spp. (Yellow Jacket) - Johannes Grosch; Christiane Hilger; Maria Beatrice Bilò; Stephanie Kler; Maximilian Schiener; Gunnar Dittmar; François Bernardin; Antoine Lesur; Markus Ollert; Carsten B. Schmidt-Weber; Simon Blank (Toxins, 2020)
Allergic reactions to stings of Hymenoptera species can have serious or even fatal consequences. If the identification of the culprit insect is possible, venom-specific immunotherapy effectively cures Hymenoptera venom allergies. Although component-resolved diagnostics has strongly evolved in recent years, the differentiation between allergies to closely related species such as Polistes dominula and Vespula spp. is still challenging. In order to generate the basis for new diagnostic and therapeutic strategies, this study aims at resolving the venom proteomes (venomes) of these species. The venoms of P. dominula and Vespula spp. (V. germanica, V. vulgaris) were analyzed by liquid chromatography-mass spectrometry. Resulting proteins were characterized regarding their function, localization and biochemical properties. The analyses yielded 157 proteins in Vespula spp. and 100 in P. dominula venom; 48 proteins, including annotated allergens, were found in both samples. In addition to a variety of venom trace molecules, new allergen candidates such as icarapin-like protein and phospholipase A2 were identified. This study elucidates the venomes of closely related allergy-eliciting Hymenoptera species. The data indicates that relying on marker allergens to differentiate between P. dominula and Vespula spp. venom allergy is probably insufficient and that strategies using cross-reactive major allergens could be more promising.